Penurunan Tekanan Darah pada Pasien Hipertensi Menggunakan Teknik Alternate Nostril Breathing Exercise - Fahri Permata; Juli Andri; Padila Padila; Muhammad Bagus Andrianto; Andry Sartika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of alternative nostril breathing exercises on reducing blood pressure in hypertensive patients in the Telaga Dewa Health Center work area, Bengkulu City. This research is quantitative research with a quasi-experimental research design. The results of the univariate analysis obtained that the respondent's age was 64 years, all genders of the respondents were found, and most of them had a family history. The results of the bivariate analysis showed that the p-value <0.05. In conclusion, there was a decrease in systolic and diastolic blood pressure before and after an alternative breathing exercise intervention in hypertension patients in the Telaga Dewa Health Center work area, Bengkulu City. Keywords: Nostril Alternative Breathing, Blood Pressure